Median Arcuate Ligament Syndrome: A Case Report - Chitrakar, Akash; Subedi, Nirajan; Bhandari, Ramesh Singh (Journal of Society of Surgeons of Nepal, 2018)
Median arcuate ligament (MAL) syndrome results from extrinsic compression of the celiac axis and or celiac ganglion by the MAL and diaphragmatic crura. A seventy five years lady presented with post prandial epigastric pain for 6 months. She had undergone considerable investigations for other diagnoses before an abdominal computed tomography (CT) revealed median arcuate ligament impinging celiac artery at its origin. She successfully underwent laparotomy and release of median arcuate ligament.